Genetically modified organism detection of insect and herbicide resistance traits by qualitative and quantitative plasmid-based methods - Khoo, Siew Ping (2012)
The employment of genetically modified organisms as food and feed products in the market is increasing dramatically from year to year. The estimated global area planted with genetically modified crops has reached 148 million heactares involving 29 countries in year 2010. Important genetically modified traits include herbicide tolerance traits encoded by the 5’-enolpyruvylshikimate-3-phosphate synthase (Cp4 epsps) gene derived from Agrobacterium sp. and insect resistance traits encoded by the cry gene derived from Bacillus thuringiensis. Worldwide commercialization of food and feed products containing the genetically modified material has raised concern from the public regarding food safety issues as well as destruction of biodiversity. Thus, many countries have established labeling legislation for genetically modified food and feed products based on a certain threshold level of their genetically modified content. The stakeholders of food and feed product companies are required to comply with the legislation to import or export their products globally. To date, several different screening and quantification assays have been developed depending on either protein or DNA as target molecules. The purpose of this study was to detect the presence of herbicide resistance Roundup ready soybean (RRS), insect resistance BT maize event 176 and insect resistance BT maize event CBH 351 (tradename StarLink corn) in food and feed products collected from the Malaysian market, by utilizing the polymerase chain reaction (PCR) assay. This study also aimed to develop a quantitative system to determine the percentage of genetically modified organism content in samples by using the SYBR Green I based real-time polymerase chain reaction assay. In this system, recombinant plasmid DNA is generated and used as a calibrator to establish calibration curves. The results from the PCR assay show that 108 out of 115 (94%) soybean containing samples were positive for the soybean lectin gene, and 45 out of 108 (42%) samples were positive for the Cp4 epsps gene specific to RRS including animal feeds (31), processed food (13) and raw soybean (1). Quantitative results showed 34 out of 45 (76%) samples certainly more than 0.9% of the Roundup ready soybean. PCR assay showed 80 out of 104 (77%) maize containing samples to be positive for the maize invertase gene; and quantitative results showed 6 samples positive for BT maize event CBH 351 and 1 sample positive for BT maize event 176. The percentage of StarLink corn certainly positive GMO samples ranged from 0.09% to 2.53%. However, the one sample positive for BT maize event 176 was shown to certain 16.90% of BT maize event 176. In conclusion, the developed qualitative and quantitative system to determine the presence of genetically modified organism in various kinds of samples in the present study could contribute towards the better post-market surveillance and facilitate the implementation of the labeling process.